A review on carbon dioxide sequestration in deep saline aquifers: Experiments, simulations, and field applications - Grant Charles Mwakipunda; Long Yu; Junwei Huang; Jinyu Tang; Riyadh I. Al-Raoush (Fuel, 2027)

Intelligent decision framework for green battery recycling: Synergistic application of machine learning and life cycle assessment - Yingshuai Ma; Youcai Zhu; Junwei Wang; Nianzi Zhang; Yang Yu; Chunguang Liu (Resources, Conservation and Recycling, 2027)

Glucose dose-dependently modulates antimicrobial peptide genes expression through the ERK/PI3K-NF-κB/FOXO signaling in Chinese mitten crab (Eriocheir sinensis) - Jinming Yu; Sixuan Li; Yuting Xi; Yiyang Xu; Chang Liu; Yuhan Tu; Siyue Li; Junwei Guo; Haidong Zou; Jinming Yuan; Yuhan Ma; Dazuo Yang; et al. (Fish & Shellfish Immunology, 2026)

Dopamine coated polycaprolactone nanospheres for prochloraz delivery to improve antifungal activity and environmental safety - Junwei Yao; Qian Wang; Chunxin Wang; Hong Qi; Qingshan Shi; Jingxia Liu; Jin Feng; Ping Yang; Manli Yu; Xiaobao Xie (Journal of Environmental Chemical Engineering, 2026)

Microecological trade-offs in partial nitritation under different ammonia-based food-to-microorganism ratios - Junwei Yang; Danyang Zhu; Enhui Xu; Linglong Shi; Rui Liu; Donghai Yang; Yu Hua; Xiaohu Dai (Journal of Environmental Chemical Engineering, 2026)

Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

Multi-omics analysis reveals the regulatory network of quality traits in green-skinned eggplant (Solanum melongena L.) - Wentao Deng; Xiaoyun Yan; Jiechun Peng; Duoduo Xiao; Kongxiu Su; Jingjing Huang; Huarong Fang; Junwei Zhang; Xinyuan Chen; Yufei Liang; Chuan Zhong; Wenjin Yu; et al. (Food Chemistry, 2026)

Copper-based nanoparticles trigger fitness decline in parasitoid wasps via gut microbiota-induced fatty acid dysregulation - Zijian Chao; Qichao Zhang; Lan Pang; Yifeng Sheng; Junwei Zhang; Ting Feng; Longtao Yu; Wenqi Shi; Zixuan Xu; Jianhua Huang; Jiani Chen (Environmental Pollution, 2026)

Sustainable fabrication of hierarchical porous carbon from bagasse via recyclable template‑coupled CO2 activation and pore structure-performance correlation in phenol adsorption - Dongsheng Li; Guangwen Xu; Yuling Shan; Junwei Ding; Wenlong Yu (Bioresource Technology, 2026)

Depth-dependent differentiation of plant- and microbial-derived carbon formation pathways drives soil organic carbon responses to straw incorporation and asymmetric warming in paddy soils - Pan Hou; Qiaogang Yu; Qi Shen; Zhaoming Chen; Qiang Wang; Jun Zhou; Xiaofang Zhu; Lijun Gao; Kangqi Lei; Jingwen Gao; Junwei Ma; Feng Wang (Plant and Soil, 2026)

The luxury effect under environmental filtering: Drivers of residential plant diversity in 15 high-altitude cities - Yao Yao; Zhiwen Gao; Lin He; Luyi Lan; Xiaoya Yu; Ruishen Yang; Junwei Wang; Yuandong Hu; Qiong La; Liangjun Da (Journal of Environmental Management, 2026)

Layer-by-layer assembly of polycationic electrolytes onto cation exchange membranes for enhanced Li+/Mg2+ selectivity: A comparative study of polyethyleneimine and chitosan - Jiadi Ying; Zhen Cui; Xiaoxiang Xi; Junwei Zhu; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Yaochun Chen; Minfeng Zeng; et al. (Desalination, 2026)

A comprehensive investigation on perovskites with different exquisite structures for oxidative coupling of methane (OCM) - Xiaomei Yu; Junwei Xu; Wenkai Ruan; Liang Guo; Jieqi Zhou; Xianglan Xu; Xiuzhong Fang; Jiating Shen; Xiang Wang (Chemical Engineering Journal, 2026)

Dynamic triaxial tests of reinforced silty clay under the combined action of freeze-thaw cycles and train loads - Jin Zhang; Jihao Yu; Chen Liu; Jiale Yang; Zihan Ma; Junwei Liu; Yingying Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Genome-wide identification of the MYB transcription factor family of blackcurrant and the key role of RnMYB44 gene in drought tolerance - Lin Wang; Xuelin Zhang; Xueying Zhao; Hongyinga Li; Jiacheng Liu; Yu Zheng; Zongya Xing; Huixin Gang; Junwei Huo; Dong Qin (Planta, 2026)

Gut microbial dysbiosis is associated with detoxification impairment in parasitoid wasps exposed to Emamectin benzoate - Longtao Yu; Lan Pang; Zixuan Xu; Yifeng Sheng; Qichao Zhang; Zijian Chao; Wenqi Shi; Ting Feng; Junwei Zhang; Jianhua Huang; Jiani Chen (Pesticide Biochemistry and Physiology, 2026)

Biocontrol potential and mechanism of a seed-endophytic Bacillus velezensis NEAU-HLD-9 against gray mold in green beans - Kuan Zhang; Xiaoyan Yu; Xinru Yang; Zhiqi Yang; Yan Zhang; Jiayi Liu; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Food Microbiology, 2026)

Radical-induced in situ covalent interfacial grafting coupled with resin infiltration enhancement for high-performance thermoplastic composites - Bowen Yu; Junwei Lyu; Wenhao Dong; Zheng Li; Jiaxiang Liu; Junhui Luo; Xiangyang Liu (Chemical Engineering Journal, 2026)

A coupled phosphorus and carbon cycling mediated by prokaryotic microbes in the deepest trench - Tianqiang Bao; Junhao Deng; Zhenzhen Li; Min Luo; Li Wang; Jiangyan Li; Guangyi Wang; Xi Yu; Ronnie N. Glud; Junwei Cao; Li Zhang; Jiasong Fang (Frontiers in Marine Science, 2026)
There has been a long-standing paradox in oceanic phosphorus (P) cycling in the ocean: high alkaline phosphatase activity (APA) persists in deep waters despite replete dissolved inorganic phosphorus (DIP), and active microbial regulatory mechanisms driving this pattern remain largely untested in the carbon-limited hadal zone. Here, we test the hypothesis that the observed elevated levels of deep-ocean APA is driven by microbial carbon demand, via full-depth water column analyses of dissolved organic phosphorus (DOP) and DIP in the Challenger Deep (Mariana Trench), combined with laboratory-based in situ-simulated high-pressure incubation experiments. We reveal two distinct phosphorus-alkaline phosphatase activity (P-APA) regulatory regimes: P-limitation-driven extreme APA in P-depleted surface waters, and sustained, elevated APA in P-replete, carbon-starved deep waters. Metabolically active alkaline phosphatase (AP)-producing taxa, most notably the SAR11 clade, were detectable throughout the full water column. Path analysis was used to evaluate the consistency of the observed data with a hypothesized causal framework linking active microbial communities, APA kinetics, and coupled phosphorus-carbon (P-C) cycling, with the model explaining 82.3% of the variance in dissolved organic carbon and 75.4% of the variance in DIP in the water column. We propose and validate a “piggyback” strategy whereby deep-sea microbes express AP to acquire carbon from DOP, offering a previously untested, potential mechanistic explanation for the long-standing deep APA paradox, while revealing a microbially mediated P-C coupling pathway that may represent a breakaway of deep-ocean carbon sequestration pathway.

A collaborative evolution strategy for dynamic multi-objective optimization based on charged individual prediction - Wenzhuo He; Jinhua Zheng; Xiaozhong Yu; Junwei Ou; Yaru Hu; Juan Zou; Kan Zhang (Swarm and Evolutionary Computation, 2026)

Sea-island polyethylene glycol/carboxylated styrene-butadiene rubber phase-change films enabled by ion-triggered inverse nanoencapsulation for flexible thermal management - Junwei Zhang; Yongkang Li; Su Xu; Liyuan Si; Jingfa Zhou; Ruiguang Xing; Huitao Yu; Xin Ge; Wei Feng (Chemical Engineering Journal, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Biocontrol effect of Bullera alba PGY-2 on postharvest black spot of pear and insights into the associated defense mechanisms - Xiaoyan Yu; Kuan Zhang; Zhiqi Yang; Bowen Guo; Xinru Yang; Yan Zhang; Jiayi Liu; Zhenhua Zhao; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Postharvest Biology and Technology, 2026)

Experimental evaluation of flexible protection for local scour mitigation around multi-bucket jacket foundations - Jijian Lian; Junwei Yu; Jiale Li; Shunyi Wang; Yaohua Guo; Xiaofeng Dong (Ocean Engineering, 2026)

Buffering failure of the ratio of secondary to primary phases: Risk overestimation of soil heavy metals under alkaline conditions - Yingdong Wu; Zixin Zeng; Rong Teng; Junwei Yang; Jiang Yu; Hui Sun; Siwei Deng; Pengxinyue Huang; Jie Luo; Yi Wu; Xuetao Zhao (Journal of Hazardous Materials, 2026)

Functional contribution and optimization of mix proportion of coal gangue, slag, and fly ash in the preparation of alkali-activated backfill materials - Ziyang Yu; Zhuangzhuang Pan; Junwei Guo; Pengfei Liu; Yi Li; Shixing Wang; Haotian Wu; Changzai Ren; Jiaxu Jin; Bo Zhang (Journal of Environmental Management, 2026)

Characterization of five Alternaria species causing leaf spot on broccoli in China - Kuan Zhang; Jiayi Liu; Zhiqi Yang; Xiaoyan Yu; Weida Li; Zhaomin Sun; Lu Chen; Jie Chen; Wensheng Xiang; Junwei Zhao; Xiangjing Wang (Physiological and Molecular Plant Pathology, 2026)

Alkali-activated fly ash catalyzed sustainable and scalable production of tough composite hydrogels toward versatile applications - Xiaowen Shi; Fengbo Zhu; Huan Zhao; Shiming Liang; Junwei Qiao; Wenwen Yu; Lan Jia; Qiang Zheng (Chemical Engineering Journal, 2026)

Preliminary Rock Brittleness Index Based on the Complete Strain–stress Curve and Mineral Composition Effects - Jin Liu; Yubo Wang; Xiao Ding; Junwei Wang; Yu Zhang; Yonglong Qu (Rock Mechanics and Rock Engineering, 2026)

Ultrasonic-assisted water washing dechlorination modified coal-based activated carbon and its adsorption performance for dyes - Yi Li; Ziyang Yu; Junwei Guo; Xianglin Li; Fan Yang; Bo Zhang (Journal of Cleaner Production, 2026)

Modification of highland barley starch properties via germination-induced amylase activation and amylopectin reduction - Yongliang Bai; Junwei Yin; Zuanhao Liang; Yu Xia; Shuyan He; Ming Yu; Haiqiang Chen (Journal of Cereal Science, 2026)

Pr-Zr-O polymorphs for catalytic methane combustion: Exploring the influence of the subcrystalline phase structure on redox sites and reactivity - Liang Guo; Junwei Xu; Xiaomei Yu; Jieqi Zhou; Rumeng Ouyang; Xiuzhong Fang; Jiating Shen; Xiang Wang (Fuel, 2026)

Extraction and spatiotemporal variation in rammed earth sites in typical arid areas of Northwest China based on multi-source remote-sensing data - Kai Cui; Li Yu; Xu Zhang; Shuang Dai; Xinghai Dang; Junwei Xu; Jianyun Zhao; Kegong Li; Xiang Zhang (International Journal of Remote Sensing, 2026)

Amino-modified gangue-derived NaX zeolite for enhanced stabilization of lead and cadmium in contaminated soils: synthesis, performance, and leaching stability - Weiwei Zhu; Jingyi Xiong; Zhuoxi Huangfu; Jiang Yu; Pengxinyue Hang; Cheng Han; Ming Chen; Bin Li; Tao Gao; Junwei Yang; Yao Du (Environmental Geochemistry and Health, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

EASNet: Edge-aware Segmentation Network for Skin Lesion Segmentation with Boundary-aware and Frequency Attention Mechanisms - Junwei Yu; Yuhe Xia; Jianping Li; Nan Liu; Haoze Li; Weiya Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

First report of Epicoccum sorghinum causing postharvest fruit rot of strawberry in China - Weiqian Zhang; Wenshuai Song; Yan Zhang; Xinru Yang; Zhiqi Yang; Xiaoyan Yu; Jie Chen; Wensheng Xiang; Xiangjing Wang; Junwei Zhao (Crop Protection, 2025)

A strategy cooperative algorithm based on state-awareness for large-scale multi-objective optimization - Hao Liu; Jinhua Zheng; Yaru Hu; Xiaozhong Yu; Junwei Ou; Juan Zou; Shengxiang Yang (Swarm and Evolutionary Computation, 2025)

Basalt visible light image recognition optimization algorithm based on YOLOv8 - Fen Jiao; Yu Yin; Xiangchuan Min; Congren Yang; Junwei Han; Qian Wei; Limin Tang; Ying Huang; Wenqing Qin (Minerals Engineering, 2025)

Tourism education in Europe and the road to Net-Zero: Are universities doing enough? - Anita Conefrey; James Hanrahan; Conor McTiernan; Maria do Rosário Borges; Joana Lima; Jaime Serra; Junwei (Jerry) Yu; María Cristina Barriuso Iglesias; M. Mercedes Galan-Ladero; Martín Gómez-Ullate; Juan-Luis Tato-Jiménez; Alina Badulescu; et al. (Journal of Cleaner Production, 2025)

Flavonoids of Lycium barbarum L. leaves alleviate DSS-induced ulcerative colitis by microbiota-gut-liver axis - Shuang Liu; Tao Zhang; Jing Ren; Jinwang Liu; Jing Fu; Junwei Yu; Yanli Fan; Yuan Liu (Food Bioscience, 2025)

Decoupling aggregation in dense protein solutions: Structural reconfiguration through disulfide reduction weakens nanoscale adhesion forces - Xueer Yu; Xiaokang Na; Wenzhe Luo; Bowen Zou; Xiaohan Zheng; Xinyao Zhao; Ziyue Wang; Junwei Zhang; Guangou Chen; Ming Du; Chao Wu (Food Chemistry, 2025)

Detection of the Development of Artificial Freezing Walls in Shield Tunnels Using GPR and Correlation Back-Projection Algorithm - Xinhao Yu; Zhuang Chen; Diansen Yang; Shaishai Zhao; Fangzheng Li; Wei Gao; Linghui Kong; Junwei Xu (Rock Mechanics and Rock Engineering, 2025)

An adaptive response algorithm based on dual-space detection for dynamic multiobjective optimization - Xiaozhong Yu; Jinhua Zheng; Yaru Hu; Junwei Ou; Juan Zou (Swarm and Evolutionary Computation, 2025)

Synergistic modification engineering for optimizing reaction kinetics of direct carbon solid oxide fuel cells with agricultural solid waste as fuel - Junwei Hou; Fengjin Yang; Junze He; Jiahong Hong; Yunjin Yang; Yuzhi Li; Jieqin Ma; Tianhao Zhong; Junming Chen; Yuancheng Luo; Yiyao Yu; Fangyong Yu; et al. (Fuel, 2025)

Advancing thermal treatment technologies for recycling end-of-life lithium-ion batteries - Yongwei Wang; Jiadong Yu; Duo Wang; Junwei Han; Hongbo Zeng (Chemical Engineering Journal, 2025)

Low-cost solar selective cooling films for endurance mileage enhancement in electric vehicles - Cheng Wang; Zhihua Zhou; Xueqing Yang; Yahui Du; Junwei Liu; Yan Liang; Yuechao Chao; Shuqi Zhang; Lu Yu; Wufan Wang; Jinyue Yan (Chemical Engineering Journal, 2025)

Fungal diversity associated with cherry leaf spot in Yantai city, Shandong province, China - Yumeng Wang; Ting Liu; Chuang Han; Xiaoyan Yu; Xi Xu; Yuhan Guo; Xinying He; Wensheng Xiang; Xiangjing Wang; Junwei Zhao (Physiological and Molecular Plant Pathology, 2025)

Application of supercritical CO2 fluid extraction technology in dealkalization and purification of high-alkali coal: Extraction process and mechanism - Junwei Guo; Xianglin Li; Yi Li; Ziyang Yu; Fan Yang; Bo Zhang (Minerals Engineering, 2025)

Mechano-kinetic integrated carbon coating enables fast-charging micro‑silicon anodes - Junwei Han; Xin Qin; Qian Xu; Lu Zhao; Debin Kong; Yun Cao; Fei Yang; Xia Hu; Yafei Wang; Mingxue Zuo; Huiyu Yu; Bocheng Yang; et al. (Chemical Engineering Journal, 2025)

Nitrogen-induced acidification increases soil organic carbon accrual by promoting particulate organic carbon and microbial necromass under long-term experiments in the paddy soils of East China - Zhaoming Chen; Qiang Wang; Jinchuan Ma; Feng Wang; Junwei Ma; Jing Ye; Ping Zou; Wanchun Sun; Qiaogang Yu (Plant and Soil, 2025)

Bioinformatics-based identification of mirdametinib as a potential therapeutic target for idiopathic pulmonary fibrosis associated with endoplasmic reticulum stress - Junwei Chen; Yuhan Du; Qi Yu; Dongyu Liu; Jinming Zhang; Tingyue Luo; Haohua Huang; Shaoxi Cai; Hangming Dong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dual-functional tight ultrafiltration membrane constructed from aminoquinone networks for sufficient dye/salt selectivity and bacterial inactivation - Riri Liu; Hanna Vanermen; Jiale Du; Qin Chen; Zijian Yu; Junwei Li; Pengrui Jin; Junfeng Zheng; Alexander Volodin; Wenyuan Ye; Raf Dewil; Ming Xie; et al. (Desalination, 2025)

Targeted nanosystems reshape the inflammatory immune microenvironment by integrated cholesterol crystal dissolution with lymphatic drainage restoration for atherosclerosis treatment - Lei Peng; Guanlun Zhou; Junwei Hu; Yutong Yao; Qian Huang; Ao Yu; Yongjian Wang (Chemical Engineering Journal, 2025)

Analysis of sinking behavior in open-ended pipe piles for marine structures: Jacking vs. hammer-driven methods - Mohsen Saleh Asheghabadi; Junwei Liu; Xiuxia Yu; Xianzhang Ling; Wenchang Shang; Hongfeng Guang (Ocean Engineering, 2025)

Reducing the building carbon emissions with quantum dot/polymer photovoltaic devices via the introduction of perovskite nanocrystals - Junwei Liu; Zhihua Zhou; Xueqing Yang; Yuechao Chao; Cheng Wang; Yahui Du; Yu Chen; Hang Yin; Jinyue Yan; Long Ye (Chemical Engineering Journal, 2025)

Long-term phosphorus addition enhances the contributions of plant lignin and microbial necromass to soil organic carbon in a rice–wheat rotation - Zhaoming Chen; Jinchuan Ma; Feng Wang; Junwei Ma; Ping Zou; Wanchun Sun; Qiaogang Yu; Qiang Wang (Applied Soil Ecology, 2025)

Experimental Study on the Hydraulic Characteristics and Shape Optimization of Ship Lock Water Conveyance Systems - Yu Duan; Dianguang Ma; Weidong Gan; Chao Ji; Junwei Zhou (Journal of Marine Science and Engineering, 2025)
To enhance the passing capacity of the Bailongtan Ship Lock on the Hongshui River, this study focused on the design scheme of its water conveyance system reconstruction and expansion project. A three-dimensional mathematical model meeting the experimental accuracy requirements was established based on the RNG k-ε turbulence model and the Volume of Fluid (VOF) free-surface tracking method. A 1:30 scale ship lock water conveyance system physical model was built and used the independently developed system for hydraulic test monitoring, acquisition, and control. Experimental research on the hydraulic characteristics and shape optimization of the water conveyance system was carried out. The experimental results show that, under the condition of a maximum head difference of 16.0 m between the upstream and downstream of the ship lock, in the design scheme, the flow in the corridor after the filling valve fails to diffuse adequately, forming a high-velocity zone and a significant pressure difference between the inner and outer sides, which poses an operational risk. By optimizing the shape of the corridor after the valve (deepening the bottom end by 2.0 m and adjusting the turning angle from 75° to 70°), the range of the high-velocity zone can be shortened from 3.0 m to 1.5 m. The pressure difference between the inner and outer sides of the corridor at the horizontal turning section is reduced by 19.2% from 5.35 m to 4.32 m of the pressure head at the moment of maximum flow rate, and the velocity in the horizontal section is less than 15 m/s. Physical model tests confirmed these improvements, with mooring forces within safety limits (longitudinal ≤ 32 kN, transverse ≤ 16 kN). The research findings indicate that integrating numerical simulation with physical model testing can effectively mitigate risks in the original design of the ship lock water conveyance system. This approach notably enhances the reliability and safety of the design scheme, as demonstrated by the significant reduction in high-velocity zones and pressure differentials. Moreover, it offers a robust scientific basis and practical technical reference for in-depth hydraulic research and targeted optimization of ship lock water conveyance systems.

First report of brown rot caused by Monilia yunnanensis on kiwiberry (Actinidia arguta) in China - Xiaoyan Yu; Zhenhua Zhao; Bowen Guo; Kuan Zhang; Jiayi Liu; Wenshuai Song; Hanxun Ju; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2025)

Genomics and biodegradation properties of an oleophilic bacterium isolated from shale oil sludge - Shuang Deng; Changfu Cai; Junwei Wang; Da Qin; Liyun Yu; Jiabin Wang; Shuang Dai; Jialin Fan; Chunlong Zhang; Liyang Li; Wei Song; Xilin Hou (International Biodeterioration & Biodegradation, 2025)

Mechanisms and characteristics of sand seepage deformation under groundwater level fluctuation scenarios - Yu Fan; Kun Huang; Junwei Wan; Hanhui Wen; Jincai Qu; Longxuan Zhang (Journal of Hydrology, 2025)

Defect BaSnO3 perovskites for oxidative dehydrogenation of ethane - Rumeng Ouyang; Junwei Xu; Jieqi Zhou; Liang Guo; Xiaomei Yu; Xiuzhong Fang; Jiating Shen; Xianglan Xu; Xiang Wang (Fuel, 2025)

Sewage sludge valorization via phytohormones production: Parameter regulation and process evaluation - Shuxian Chen; Yu Hua; Qi Song; Xin Yuan; Junwei Yang; Yue Zhang; Xiaohu Dai (Water Research, 2025)

Correlation between microbial communities and flavor compounds in Suantangzi dough from Liaoning Province, China - Weina Song; Huifei Yi; Fei Lu; Yu Deng; Minpeng Zhu; Junwei Wang; Xiuhong Zhao; Zhigang Xiao; Yifan Zhang (Food Chemistry, 2025)

Ficus pumila fruit polysaccharide alleviates OVA-induced allergic asthma mice through the MAPK/NF-κB signaling pathway - Xiaomei Ye; Shiru Mo; Chengyuan Wang; Qiang Yu; Yi Chen; Junwei Zhao; Mingyue Shen; Jilan Jiao; Xiaoyan Ou; Jianhua Xie (Food Bioscience, 2025)

Oxygen-induced evolution of anammox granular sludge explains its unique responses during preservation - Leiyan Guo; Chao Pan; Junwei Wu; Yang Yu; Dongdong Xu; Wenda Chen; Wenji Li; Ping Zheng; Meng Zhang (Water Research, 2024)

Effects of fishing stress on fatty acid and amino acid composition and glycolipid metabolism in triploid rainbow trout - Banghua Xia; Dandan Zhao; Qirui Hao; Junfei Yu; Yue Han; Ling Ling; Rongwei Zhao; Junwei Zhao (Food Chemistry, 2024)

Lignite-derived carbonized polymer dots for oilfield tracers - Mingjin Du; Channa Wang; Yilin Zhu; Chao Ma; Jiangtao Wang; Gang Chang; Mengyu Sun; Tongsiliu Wu; Yu Xiao; Zheng Zhao; Junwei Su; Xiangdong Ding; et al. (Chemical Engineering Journal, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

Effect of antibiotic perturbation on nitrous oxide emissions: An in-depth analysis - Wenjun Yu; Kashif Hayat; Junwei Ma; Xiaoping Fan; Yuyi Yang; Zulin Zhang; Qiaogang Yu; Mingrong Qian; Hui Lin (Critical Reviews in Environmental Science and Technology, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Incorporation of TC4 (Ti-6Al-4V) to construct strong interfacial bonding with Mg matrix to achieve improved hydrogen storage kinetics - Bin Li; Xuhao Peng; Kun Yang; Qianfeng Liao; Guobing Wei; Junwei Liu; Yan Yang; Yu’an Chen; Fusheng Pan (Chemical Engineering Journal, 2024)

Identification and evaluation of an endophytic antagonistic yeast for the control of gray mold (Botrytis cinerea) in apple and mechanisms of action - Xiaoyan Yu; Kuan Zhang; Jiayi Liu; Zhenhua Zhao; Bowen Guo; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Food Microbiology, 2024)

Polypyrrole as photo-thermal-assisted modifier for BiVO4 photoanode enables high-performance photoelectrochemical water splitting - Jingnan Zhang; Tongxin Tang; Zezhong Xie; Yu-xin Chen; Hao Yang; Kai-Hang Ye; Junwei Chen; Wenhao Zou; Jianxin Shi; Yongchao Huang (Chemical Engineering Journal, 2024)

Experimental Investigation of Freezing Front Detection Behind Shield Tunnel Segments Using Ground-Penetrating Radar - Xinhao Yu; Wei Gao; Fangzheng Li; Diansen Yang; Hang Ding; Jiwei Zhang; Lei Wang; Junwei Xu (Rock Mechanics and Rock Engineering, 2024)

Fruit rot on tomatoes caused by Talaromyces stipitatus newly reported in China - Lan Wang; Xiaoyan Yu; Bowen Guo; Qing Li; Kangdi Lai; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2024)

Analysis on dust prevention law of new barrier strategy in fully mechanized coal mining face - Junwei Zhao; Haiming Yu; Hui Dong; Sen Xie; Yu Cheng; Zongwei Xia (Process Safety and Environmental Protection, 2024)

The coupling of sulfide and Fe-Mn mineral promotes the migration of lead and zinc in the redox cycle of high pH floodplain soils - Qianqian Yu; Junwei Wen; Sili Zhang; Chen Wu; Hao Ouyang; Nannan Hu; Xu Li; Xinhong Qiu (Journal of Hazardous Materials, 2024)

Pre-introducing Li4NiWO6 defect phase by tungsten modification enables highly stabilized Ni-rich cathode - Fanghui Du; Hanyu Qu; Xiaoxuan Yu; Lei Ding; Pengfang Zhang; Yan Wang; Yuling Chen; Yingchao Wang; Xitong Zhang; Junwei Zheng (Chemical Engineering Journal, 2024)

Experimental Study on Cyclic Simple Shear Test of Coastal Tidal Soft Soil - Xiuxia Yu; Honglei Sun; Junwei Liu; Hongxuan Zhao; Yu Han (Journal of Marine Science and Engineering, 2024)
Based on undrained cyclic simple shear tests conducted on coastal tidal soft soil under various conditions of cyclic stress ratios and moisture contents, this study investigated the influence of these factors on the dynamic properties of the soil. The findings indicated that with increasing moisture content and stress cycle ratio, the stress–strain hysteresis loop gradually expanded, resulting in a higher strain difference and a transition from a dense to a sparse curve pattern. Moreover, the symmetry of the hysteresis loop was lost in the later stages of shearing. With an increase in the number of cycles, the cumulative shear strain gradually increased, and the increase in the cyclic ratio of water content to stress reduced the number of cyclic shear cycles required to achieve failure, thereby accelerating the soil’s failure rate. A predictive formula was developed based on the experimental results to estimate the failure cycles as a function of the cyclic stress ratio and moisture content. Furthermore, the softening index decreased gradually with an increasing number of cycles, and a higher moisture content and cyclic stress ratio accelerated the soil’s softening process. It was observed that under the conditions of optimal moisture content, the soil exhibited a slower softening rate during the initial stage of shearing.

Transcriptional and ultrastructural changes of macrophages after african swine fever virus infection - Cong Yuan; Yueyue Duan; Xiangtong Li; Yu Zhang; Liyan Cao; Tao Feng; Junwei Ge; Qi Wang; Haixue Zheng (Veterinary Microbiology, 2024)

Rhizosphere microbes influence wogonoside accumulation in perennial Scutellaria baicalensis - Yang SUN; Hong LIU; Junwei PENG; Minchong SHEN; Yang HU; Dongsheng YU; Jiangang LI; Yuanhua DONG (Pedosphere, 2024)

Ultra-low viscosity betaine hydrochloride-formic acid deep eutectic solvent for leaching critical metals from spent NCM lithium-ion batteries - Chunli Liu; Jinxiang Yu; Jia Hu; Jianbin Xu; Ao Yu; Tingting Liu; Zhongbing Wang; Xubiao Luo; Chunjian Deng; Feng Luo; Junwei He; Guisheng Zeng (Journal of Environmental Chemical Engineering, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Dipole-induced hydrogen bonds enhanced P/O co-doped Lyocell-based porous carbon fiber cloth for hydrogen storage under ambient pressure - Jialin Li; Yu Wang; Ye Zhang; Wei Zhao; Wenzhe Bao; Yufeifan Duan; Junwei Yu; Bo Zhu; Kun Qiao (Chemical Engineering Journal, 2024)

Systematic review on the residual chemicals in wastewater treatment sludge: Specifically focusing on the occurrence state and anaerobic bioprocess - Junwei Yang; Linglong Shi; Xiang Chen; Xiaoyi Huang; Xiankai Wang; Shuxian Chen; Yu Hua; Hui Gong; Bin Dong; Huiling Liu; Xiaohu Dai (Chemical Engineering Journal, 2024)

Physical Experimental Study on the Wave Reflection and Run-Up of a New Ecological Hollow Cube - Haitao Zhao; Feiyue Ding; Junwei Ye; Huabin Jiang; Wei Chen; Weifang Gu; Gengfeng Yu; Qiang Li (Journal of Marine Science and Engineering, 2024)
Implementing quadrangular hollow blocks on breakwaters is a common method for wave mitigation and ocean disaster prevention. In order to improve the wave-damping performance of conventional quadrangular hollow blocks, a new quadrangular hollow block is proposed. In this study, a series of physical modeling experiments were conducted in a two-dimensional wave flume to investigate the wave reflection and wave run-up height of a new quadrilateral hollow block under regular wave action. Test results showed that wave reflection and wave run-up height decreased with the breakwater slope. The wave run-up height increased with wave height, and the reflection coefficient decreased with wave height. Wave reflection and run-up height increased with the wave period. The reflection coefficient of the new quadrangular hollow blocks was lower than that of the conventional quadrangular hollow blocks and decreased with frame height. In addition, this study found that the reflection coefficient and relative run-up height increased with the average wave breaking parameter. The new quadrilateral hollow block has advantages in wave mitigation compared to the conventional quadrilateral hollow block.

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Effects of resveratrol on DLD and NDUFB9 decrease in frozen semen of Mongolian sheep - Yuting Chen; Fanhua Meng; Yang Liu; Chunxiao Zhu; Yu Ling; Chunxia Liu; Lu Li; Yongbin Liu; Xiaolong He; Junwei Cao; Yanru Zhang (Cryobiology, 2024)

Dynamics of rhizosphere microbial structure and function associated with the biennial bearing of moso bamboo - Yu Wang; Bing Wang; Jianwei Chen; Lei Sun; Yinguang Hou; Yayu Wang; Jiongliang Wang; Junwei Gan; Rutwik Barmukh; Shanying Li; Zeyu Fan; Pengfei Bao; et al. (Journal of Environmental Management, 2024)

Micromechanical investigation of the effect of an imposed stress state change during drained cyclic loading using DEM - Bo Liu; Zhiyong Liu; Junwei Jin; Zhen-Yu Yin (Computers and Geotechnics, 2024)

A flexibility self-powered Band-Aid for diabetes wound healing and skin bioelectronics - Lingshun Sun; Zhiwei Wang; Haifei Kang; Peiyuan Luo; Junwei Su; Wenying Wei; Peiqian Zhou; Aixi Yu; Honglian Dai (Chemical Engineering Journal, 2024)

Neonicotinoid insecticide imidacloprid induces chemosensory deficits in a nontarget parasitoid wasp - Wenqi Shi; Qichao Zhang; Yifeng Sheng; Zhi Dong; Ting Feng; Junwei Zhang; Longtao Yu; Zixuan Xu; Lan Pang; Jiani Chen; Xuexin Chen; Jianhua Huang (Science of The Total Environment, 2024)

Integrating recycled valuable elements from spent LiFePO4 batteries based on a dimethyl oxalate leaching system - Chunli Liu; Jianbin Xu; Jinxiang Yu; Jia Hu; Pengfei Liu; Zhongbing Wang; Chunjian Deng; Feng Luo; Junwei He; Guisheng Zeng; Xubiao Luo (Resources, Conservation and Recycling, 2024)

Study on the transport and deposition of micron-sized particles with different densities in the coal mine environment in miners - Yu Cheng; Haiming Yu; Yuxi Ye; Yao Xie; Junwei Zhao; Sen Xie (Fuel, 2024)

Anthocyanins-natural pigment of colored rice bran: Composition and biological activities - Ting Chen; Liuming Xie; Gang Wang; Jilan Jiao; Junwei Zhao; Qiang Yu; Yi Chen; Mingyue Shen; Huiliang Wen; Xiaoyan Ou; Jianhua Xie (Food Research International, 2024)

Leaf spot on cucumber caused by Stemphylium vesicarium newly reported in China - Xiaoyan Yu; Rui Han; Weiqian Zhang; Zhihua Li; Xue Zhang; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2023)

Affinity difference determines the assembly and interaction mode of anammox community reconstructed by siderophores - Ziyang Dong; Yuxin Ma; Mengwen Yu; Yufei Cai; Yingluo Chen; Junwei Wu; Fang Ma; Baolan Hu (Science of The Total Environment, 2023)

Numerical study on the dynamic response of liquid-filled closed hollow cylinder under water impact - Kuo Yuan; Junwei Yu; Zheng He; Hang Yu; Fanchen Meng (Ocean Engineering, 2023)

Surface engineering based on element interdiffusion and interfacial reactions to boost the performance of LiCoO2 cathode material - Fanghui Du; Zhongxu Fan; Lei Ding; Yan Wang; Wenjing Shi; Jie Zhang; Hanyu Qu; Xiaoxuan Yu; Yuling Chen; Junwei Zheng (Chemical Engineering Journal, 2023)

Dynamic characteristics of heavy metal accumulation in agricultural soils after continuous organic fertilizer application: Field-scale monitoring - Wanchun Sun; Jing Ye; Hui Lin; Qiaogang Yu; Qiang Wang; Zhaoming Chen; Jinchuan Ma; Junwei Ma (Chemosphere, 2023)

Hybrid prediction model for cold load in large public buildings based on mean residual feedback and improved SVR - Haiyan Liu; Junqi Yu; Junwei Dai; Anjun Zhao; Meng Wang; Meng Zhou (Energy and Buildings, 2023)

Epicoccum sorghinum as leaf spot disease-causing pathogen in ginger (Zingiber officinale Rosc.) in China - Xiaoyan Yu; Zhihua Li; Rui Han; Weiqian Zhang; Jing Zhang; Weiyue Cao; Yue Ma; Xiangjing Wang; Junwei Zhao; Wensheng Xiang (Crop Protection, 2023)

Environmental governance, executive incentive, and enterprise performance: Evidence from Chinese mineral enterprises - Xiaoli Hao; Shufang Wen; Ke Li; Junwei Wu; Haitao Wu; Yu Hao (Resources Policy, 2023)

Direct degradation of Bisphenol A from aqueous solution by active red mud in aerobic environment - Zhicheng Chen; Xinhong Qiu; Jun Ke; Junwei Wen; Chen Wu; Qianqian Yu (Environmental Science and Pollution Research, 2023)

MOF-derived nano CaO for highly efficient CO2 fast adsorption - Zixiao Liu; Yonglian Lu; Chunfen Wang; Yu Zhang; Xiaodie Jin; Junwei Wu; Youhe Wang; Jingbin Zeng; Zifeng Yan; Hongman Sun; Chunfei Wu (Fuel, 2023)

Exploring the structure–reactivity relationship of sn-Cr binary catalysts with XRD extrapolation method: The vital role of surface O2− and acidic sites for toluene combustion - Haiming Yan; Yu Lv; Tianyi Xing; Shijing Zhang; Xianglan Xu; Junwei Xu; Xiuzhong Fang; Xiang Wang (Fuel, 2023)

Influence mechanism of wheat bran cellulose and cellulose nanocrystals on the storage stability of soy protein isolate films: Conformation modification and molecular interaction perspective - Yaqing Xiao; Huajian Xu; Qianxin Zhou; Weixiao Li; Junwei Gao; Xiangxin Liao; Zhenyu Yu; Mingming Zheng; Yibin Zhou; Xiaonan Sui; Yingnan Liu (Food Hydrocolloids, 2023)

Soil pH change induced by smelting activities affects secondary carbonate production and long-term Cd activity in subsoils - Junwei Wen; Chen Wu; Xiangyang Bi; Sili Zhang; Hao Ouyang; Jiaxin Ye; Toshihiko Ohnuki; Qianqian Yu (Applied Geochemistry, 2023)

Influence law of structural parameters of pressure-swirl nozzle on atomization effect based on multiscale model - Yao Xie; Yuxi Ye; Haiming Yu; Weimin Cheng; Sen Xie; Junwei Zhao (Environmental Science and Pollution Research, 2023)

Study on the coal dust deposition fraction and site in the upper respiratory tract under different particle sizes and labor intensities - Yu Cheng; Haiming Yu; Sen Xie; Junwei Zhao; Yuxi Ye (Science of The Total Environment, 2023)

Improved phosphorus availability and reduced degree of phosphorus saturation by biochar-blended organic fertilizer addition to agricultural field soils - Junwei Jin; Yunying Fang; Shuang He; Yu Liu; Chunlong Liu; Fayong Li; Sangar Khan; Kamel Mohamed Eltohamy; Boyi Liu; Xinqiang Liang (Chemosphere, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

Encapsulating selenium into mesoporous carbon for high-performance aqueous Cu-Se battery - Zhouxiang Wu; Xia Lin; Junwei Zhang; Xiquan Chu; Jiaxi Xu; Jing Li; Yiwen Liu; Haoxiang Yu; Lei Yan; Liyuan Zhang; Jie Shu (Chemical Engineering Journal, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

Review and prospects of mining chemical dust suppressant: classification and mechanisms - Hui Dong; Haiming Yu; Rongxiao Xu; Weimin Cheng; Yuxi Ye; Sen Xie; Junwei Zhao; Yu Cheng (Environmental Science and Pollution Research, 2023)

Double Broad Reinforcement Learning Based on Hindsight Experience Replay for Collision Avoidance of Unmanned Surface Vehicles - Jiabao Yu; Jiawei Chen; Ying Chen; Zhiguo Zhou; Junwei Duan (Journal of Marine Science and Engineering, 2022)
Although broad reinforcement learning (BRL) provides a more intelligent autonomous decision-making method for the collision avoidance problem of unmanned surface vehicles (USVs), the algorithm still has the problem of over-estimation and has difficulty converging quickly due to the sparse reward problem in a large area of sea. To overcome the dilemma, we propose a double broad reinforcement learning based on hindsight experience replay (DBRL-HER) for the collision avoidance system of USVs to improve the efficiency and accuracy of decision-making. The algorithm decouples the two steps of target action selection and target Q value calculation to form the double broad reinforcement learning method and then adopts hindsight experience replay to allow the agent to learn from the experience of failure in order to greatly improve the sample utilization efficiency. Through training in a grid environment, the collision avoidance success rate of the proposed algorithm was found to be 31.9 percentage points higher than that in the deep Q network (DQN) and 24.4 percentage points higher than that in BRL. A Unity 3D simulation platform with high fidelity was also designed to simulate the movement of USVs. An experiment on the platform fully verified the effectiveness of the proposed algorithm.

Cellulomonas triticagri sp. nov., isolated from the rhizosphere soil of wheat (Triticum aestivum L.) - Chuanyu Han; Yuting Zhang; Bing Yu; Qiqi Shan; Junwei Zhao; Haoran Shi; Yuanyuan Tian; Yan Zhang; Chunyu Zhu; Wensheng Xiang (Archives of Microbiology, 2022)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

Simultaneous visual diagnosis of acute hepatopancreatic necrosis disease and Enterocytozoon hepatopenaei infection in shrimp with duplex recombinase polymerase amplification - Pei Wang; Chao Ma; Lei Liao; Junwei Yu; Longyu Yi; Yi Qiao; Xin Liu; Song Gao; Hui Shen; Qunwei Lu (Journal of Fish Diseases, 2021)
Shrimp is a globally popular seafood. Shrimp farming has been challenged by various infectious diseases that lead to significant economic losses. The prevention of two important shrimp infectious diseases, the acute hepatopancreatic necrosis disease (AHPND) and the Enterocytozoon hepatopenaei (EHP) infection, is highly dependent on early and accurate diagnostic. On‐site monitoring of the two diseases in shrimp farming facilities demands point‐of‐care‐testing (POCT) type of diagnostic assays. This study established a duplex recombinase polymerase amplification (RPA) and lateral flow dipstick (LFD) combined assay that could simultaneously diagnose the two diseases. The optimized RPA‐LFD assay could finish the diagnostic in 35 min with good specificity, and the sensitivity reached 10 1 and 10 2 gene copies per reaction for EHP and AHPND, respectively, which were at the same level as the currently available molecular diagnostic assays. Test results of clinical samples showed 100% agreement of this assay with the industrial standard nested polymerase chain reaction (PCR) assays, and samples with both diseases were simultaneously identified. Because of the isothermal 37℃ amplification and the visual reading of the signal on dipsticks, the dependence on equipment is minimal. This duplex RPA‐LFD assay is well suited for simultaneous POCT diagnostic of the two important shrimp infectious diseases. Moreover, the principle can be applied to multiplex POCT diagnostic of other infectious diseases in aquaculture.

Effect of Quicklime on Microbial Community in Strong Acidic Soil - Junwei Liang; Xiangquan Yu; Yafan Cao; Jiguang Zhang; Ning Yan; Lin Xue; Xianjie Cai; Guoming Shen (Journal of Soil Science and Plant Nutrition, 2021)

Herbidospora solisilvae sp. nov., a novel cellulose-degrading actinobacterium isolated from forest soil - Mingying Yu; Rui Zhou; Jingjing Li; Liyuan Han; Han Wang; Siyu Zhang; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Antonie van Leeuwenhoek, 2021)

Influences of organic material application on the physically separated soil organic carbon and nitrogen fractions in rice fields - Qiaogang Yu; Jing Ye; Wanchun Sun; Hui Lin; Qiang Wang; Junwei Ma (Journal of Soils and Sediments, 2021)

Chemical constituents from Glehnia littoralis and their chemotaxonomic significance - Shouwen Zhang; Fang Cheng; Li Yang; Jinxiang Zeng; Fengyu Han; Xiuling Yu; Yuye Zhu; Guoyue Zhong; Junwei He (Natural Product Research, 2020)

Design and Application of Buoy Single Point Mooring System with Electro-Optical-Mechanical (EOM) Cable - Junwei Yu; Shaowei Zhang; Wencai Yang; Yongzhi Xin; Huaining Gao (Journal of Marine Science and Engineering, 2020)
This paper presents the design of a hybrid system named the Mooring Buoys Observation System for Benthic with Electro Optical Mechanical Cable (MBOSBC) for long-term mooring buoy observation in deep oceans. MBOSBC is comprised of three main modules: a surface buoy, a benthic node, and an Electro-Optical-Mechanical (EOM) cable. The Surface buoy provides energy for the entire system, the Benthic node is used to observe scientific phenomena on the seabed, and the Electro-Optical-Mechanical (EOM) cable connects the sea surface buoy and the benthic observation node, serving as the information and power transmission link. This paper provides design criteria for a single point mooring buoy using an EOM cable. The environmental load of the buoy under varying wind, wave, and current conditions is analyzed and the mooring hydrodynamic force of EOM is calculated. After calculating the load of the EOM cable under extreme marine conditions, the hydrodynamic force needed for the system is analyzed. After physically testing the strength of the designed EOM cable, a near-shore test of MBOSBC was carried out, in order to verify that the system has the expected function.

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

Detection and molecular characterization of canine circovirus circulating in northeastern China during 2014–2016 - Lingdi Niu; Zheng Wang; Lili Zhao; Yu Wang; Xingyang Cui; Yunjia Shi; Hongyan Chen; Junwei Ge (Archives of Virology, 2020)

Microbispora tritici sp. nov., a novel actinomycete isolated from a root of wheat (Triticum aestivum L.) - Chuanyu Han; Junwei Zhao; Bing Yu; Haoran Shi; Chen Zhang; Xiaowei Guo; Wensheng Xiang; Xiangjing Wang (Antonie van Leeuwenhoek, 2019)

Rabbit’s Host Defense Peptide (RSRAH) Protects Mice from Escherichia coli Challenge - Hongwei Chen; Junwei Wu; Yidong Wang; Xiang Yu; Tao Feng; Depeng Dai; Mengling Xiang; Lijuan Chen (International Journal of Peptide Research and Therapeutics, 2019)

Impacts of various types of El Niño–Southern Oscillation (ENSO) and ENSO Modoki on the rainy season over the Huaihe River basin - Qing Cao; Zhenchun Hao; Junwei Zhou; Wenzhuo Wang; Feifei Yuan; Wenbin Zhu; Chao Yu (International Journal of Climatology, 2019)
Precipitation is a significant parameter in many aspects such as agriculture, water management and climate variability. To characterize rainy season variations is important to understand precipitation variability under the effect of climate change. In this study, rainy season features (i.e., onset, retreat and rainy‐season precipitation) over the Huaihe River basin (HRB) and the response to different types of El Niño–Southern Oscillation (ENSO), that is, central Pacific warming (CPW), eastern Pacific warming (EPW), eastern Pacific cooling (EPC), conventional ENSO and ENSO Modoki in the developing and decaying phases are evaluated. The multi‐scale moving t test was used to capture onset and retreat of rainy season. The possible dynamic causes of ENSO‐induced precipitation over the HRB, such as monsoon and atmospheric circulation, were also explored. Results show that (a) onset (retreat) of rainy season progressed northwards (westwards), with rainy‐season precipitation increasing from north to south; (b) rainy‐season precipitation showed a strong correlation to Sea Surface Temperature (SST) in Niño regions. Dry and wet signals were identified in different regions of the HRB in the developing and decaying phases of CPW, EPC and EPW. Special attention should be paid on decaying EPW, where totally dry signals were found, which can reach down to 25% below average precipitation; (c) developing El Niño Modoki and decaying El Niño showed totally dry signals, with decaying El Niño Modoki and conventional La Niña demonstrating overall increasing precipitation; (d) different performances of ENSO‐induced precipitation during rainy season over the HRB are attributable to the combined influences of the monsoon from the India Ocean and the anticyclonic flow in the western North Pacific (WNP). Stronger anticyclone and monsoon are generally associated with increasing rainy‐season precipitation. These results can improve predictability of rainy season features and ENSO‐induced precipitation over the Huaihe River basin.

Temporal‐spatial pattern of organic carbon sequestration by Chinese lakes since 1850 - Mei Wang; Jianghua Wu; Huai Chen; Zicheng Yu; Qiu'an Zhu; Changhui Peng; Nicholas John Anderson; Junwei Luan (Limnology and Oceanography, 2018)
In the last century, lakes in China have been subject to forcing by climate change, intensification of agriculture, and urban expansion, though their effects on lake OC sequestration are poorly understood. We compiled dry mass and OC burial rates from 82 210 Pb‐dated lake sediment records in China. The average post‐1950 focusing‐corrected lake mass accumulation rate (MAR FC ) of 256 ± 56 g m −2 yr −1 (median ± SE) and focusing‐corrected OC accumulation rate (CAR FC ) of 8 ± 3 g C m −2 yr −1 were significantly higher than the 1850–1900 rates ( p FC was most marked in the subtropical lakes of the East Plain (EP) and on the Yunnan‐Guizhou Plateau (YG), where the post‐1950 CAR FC was about three times that of the 1850–1900 ( p FC was significantly higher in the EP than that on the Mongolia‐Xinjiang Plateau (MX) for all time periods ( p FC in YG was significantly higher than rates in the Qinghai‐Tibetan Plateau (QTP) for the post‐1950 and MX for the 1850–1900 ( p FC varied among regions, with catchment climate variables the most important regulators in MX, Northeast China, and QTP, but the in‐lake nutrient concentrations were more important in YG and EP ( p

Commonly preserved and species-specific gyral folding patterns across primate brains - Xiao Li; Hanbo Chen; Tuo Zhang; Xiang Yu; Xi Jiang; Kaiming Li; Longchuan Li; Mir Jalil Razavi; Xianqiao Wang; Xintao Hu; Junwei Han; Lei Guo; et al. (Brain Structure and Function, 2017)

Influences of Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on Heavy Metals and Inorganic Nitrogen Transformation in the Rice Field Surface Water - Qiaogang Yu; Junwei Ma; Wanchun Sun; Hui Lin; Qiang Wang; Jianrong Fu (Water, Air, & Soil Pollution, 2017)

The Anti-Melanoma Efficiency of the Intratumoral Injection of Cucurbitacin-Loaded Sustained Release Carriers: In Situ-Forming Implants - Jianbo Guo; Junwei Wang; Chenchen Cai; Jinghua Xu; Hongdan Yu; Hui Xu; Tang Xing (AAPS PharmSciTech, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

Soil microbial systems respond differentially to tetracycline, sulfamonomethoxine, and ciprofloxacin entering soil under pot experimental conditions alone and in combination - Junwei Ma; Hui Lin; Wanchun Sun; Qiang Wang; Qiaogang Yu; Yuhua Zhao; Jianrong Fu (Environmental Science and Pollution Research, 2014)

Erratum to: Streptomyces polyrhachii sp. nov., a novel actinomycete isolated from an edible Chinese black ant (Polyrhachis vicina Roger) - Chao Yu; Chongxi Liu; Xiangjing Wang; Junwei Zhao; Lingyu Yang; Ruixia Gao; Yuejing Zhang; Wensheng Xiang (Antonie van Leeuwenhoek, 2014)

Micromonospora jinlongensis sp. nov., isolated from muddy soil in China and emended description of the genus Micromonospora - Ruixia Gao; Chongxi Liu; Junwei Zhao; Feiyu Jia; Chao Yu; Lingyu Yang; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2014)

Streptomyces polyrhachii sp. nov., a novel actinomycete isolated from an edible Chinese black ant (Polyrhachis vicina Roger) - Chao Yu; Chongxi Liu; Xiangjing Wang; Junwei Zhao; Lingyu Yang; Ruixia Gao; Yuejing Zhang; Wensheng Xiang (Antonie van Leeuwenhoek, 2013)

Antisense MMP-9 RNA inhibits malignant glioma cell growth in vitro and in vivo - Cuiyun Sun; Qian Wang; Hongxu Zhou; Shizhu Yu; Alain R. Simard; Chunsheng Kang; Yanyan Li; Yanling Kong; Tongling An; Yanjun Wen; Fudong Shi; Junwei Hao (Neuroscience Bulletin, 2013)

Meta-Analysis of Functional Roles of DICCCOLs - Yixuan Yuan; Xi Jiang; Dajiang Zhu; Hanbo Chen; Kaiming Li; Peili Lv; Xiang Yu; Xiaojin Li; Shu Zhang; Tuo Zhang; Xintao Hu; Junwei Han; et al. (Neuroinformatics, 2013)

RAB-27 and its effector RBF-1 regulate the tethering and docking steps of DCV exocytosis in C. elegans - WanJuan Feng; Tao Liang; JunWei Yu; Wei Zhou; YongDeng Zhang; ZhengXing Wu; Tao Xu (Science China Life Sciences, 2012)

Overexpression of survivin and cyclin D1 in CHO cells confers apoptosis resistance and enhances growth in serum-free suspension culture - Xinghui Zhao; Junwei Guo; Yingqun Yu; Shaoqiong Yi; Ting Yu; Ling Fu; Lihua Hou; Wei Chen (Biotechnology Letters, 2011)